« Criar hombres y no fieras », civilité et construction d’une masculinité hégémonique (Espagne, 1787-1868) - Marie Walin (Genre, Sexualité et Société)
From the end of the 18th century to the liberal revolution of 1868, liberalism has taken an important place in the Spanish political landscape, as a political movement as well as a new way of understanding the social world. Liberal political parties played a strong part in the process of redefinition of social norms, with the aim of imposing a new hegemony (Gramsci, 1979-1992). This strategy was mainly developed through the organization of the first public education system, set up in 1838. This paper analyzes conduct books, one of the most important instruments of this system, to show how masculine bodies were used to create consent to liberal hegemony. In particular, it aims to show that the liberal social project contains a model of “hegemonic masculinity” (Connell, 1995) that is taught to the working class to impose global relationships of dominance. From the end of the 18th century to the liberal revolution of 1868, liberalism has taken an important place in the political Spanish landscape, as a political movement as well as a new way of understanding the social world. Liberal political parties played a strong part in a process of redefinition of social norms, with the aim of imposing a new hegemony (Gramsci, 1979-1992). This strategy was mainly developed through the organization of the first public education system set up since 1838. This paper analyzes conduct books, one of the most important instruments of this system, to show how masculine bodies were used to create consent to liberal hegemony. In particular, it aims to show that the liberal social project contains a model of “hegemonic masculinity” (Connell, 1995) in which teaching to popular class is used to impose global relationships of dominance.